ENT 530 Social Media Portfolio / Noor Atikah Suyono - Suyono, Noor Atikah (2019)
Chocojar is the one of the most popular snakes in Malaysia. Chocojar with the slogan "Delicious Yet Filling" is located near Selangor with address No 18, Jalan PPSL2, Pusat Pemiagaan Sungai Lias, 45300 Sungai Besar, Selangor. Chocojar Crispy Letopzz si my business name in social media portfolio. The type of business for my social media portfolio is food. Before this I have sold many things that related to the food but I am not sure and clear the strategies. I have started the online business just want to get the experience and trying something new to learn. But after guidance from the lecturer and the knowledge I gained from this subject to make some strategies to make good sales. So I put courage and tried to start selling the new product with some strategies on online business. Finally, my new business Chocojar Crispy Letopzz which is four flavour with some of topping I have provided to the customer going well. For a brief explanation, I have created a business name on facebook page after survey the things what to sell for this individual's business. After survey I got that chocojar are quite famous among teenagers especially students. It is quite difficult to flow the process as we are as students, but with determination I can achieved my target in one time. I also make frequently posts on social media through WhatsApps and Facebook to get more customers for buying this chocojar. In addition to frequent post, I have also to do some hard sell and soft sell to attract customers to promote my design and also my product.